Pelaksanaan Pengajian Mujahadah Kamis Wage Bagi Peningkatan Kualitas Bacaan Berbahasa Arab Jamaah - Muhammad Nasrudin; M. Hadi Manshur; Nginayatul Khasanah; Ahmad Turmudzi (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2021)
Pengajian Mujahada Kamis Wage has become an important part in the study of Islam at the Pandanaran Islamic Boarding School, Sleman Regency. The teaching of Islam through the inculcation of religious norms in these activities as well as reading the Koran, which requires the conformity of the Arabic word and meaning for the participants and congregation of the recitation. Qualitative exploratory research to obtain the natural setting also identifies how the organizers overcame these obstacles to obtain quality Islamic reading in Arabic from the congregation. PMKW at Pesantren PPSP is implemented openly without limitation on the religious qualifications of participants. However, they are required to be able to pronounce and understand because most of the material is in Arabic, as the main language in Islam. To reduce misunderstandings and make it easier for pilgrims, the organizers have taken several anticipatory steps. An important action is the publication of a book of Mujahadah reading material which is not only written in Arabic, but is also equipped with a reading method even complete with its meaning. In addition, to equalize the intonation of the mujahadah reading material, the congregation was also directly led by one instructor.